2022
DOI: 10.1161/strokeaha.121.036038
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Vascular Brain Lesions in Young Adults With Acute Ischemic Stroke

Abstract: Background and Purpose: Subclinical vascular brain lesions are highly prevalent in elderly patients with stroke. Little is known about predisposing factors and their impact on long-term outcome of patients with stroke at a young age. Methods: We quantified magnetic resonance-defined subclinical vascular brain lesions, including lacunes and white matter hyperintensities, perivascular spaces and cerebral microbleeds, and assessed total small-vessel diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…CSVD contributes to significant morbidity and mortality through its impact on stroke risk, cognitive decline, and dementia. Small vessel disease accounts for approximately 22% of ischemic stroke, and small vessel disease burden increases the risk of recurrent stroke following ischemic or hemorrhagic stroke 1-4 . CSVD manifests as “silent” brain infarcts as well as clinically recognized small vessel ischemic strokes.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…CSVD contributes to significant morbidity and mortality through its impact on stroke risk, cognitive decline, and dementia. Small vessel disease accounts for approximately 22% of ischemic stroke, and small vessel disease burden increases the risk of recurrent stroke following ischemic or hemorrhagic stroke 1-4 . CSVD manifests as “silent” brain infarcts as well as clinically recognized small vessel ischemic strokes.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Etiology and risk factors [45,80,82,98,[104][105][106][107][108][109][110][111][112][113][114][115][116][117] FHS was consistently associated with small vessel disease [80,82,[104][105][106][107][108] and large vessel disease [80,98,[105][106][107][108], but not with cardioembolic etiology [45,116,117].…”
Section: Parameter Publications Correlationmentioning
confidence: 99%
“…With regards to stroke etiology, authors consistently reported an association of FHS with small vessel disease [80,82,[104][105][106][107][108], subclinical lacunes [109,110], intracranial artery stenosis [111][112][113][114][115] and large vessel disease [80,98,[105][106][107][108], but not with cardioembolic stroke [45,116,117]. One paper found that FHS was related to lacunar stroke in older subjects and cryptogenic etiology in the younger [118].…”
Section: Type Of Stroke Etiology and Interaction With Risk Factorsmentioning
confidence: 99%
“…The inflammation and immune response theory elucidates the mechanism of the immune system’s mechanism in response to harmful stimuli like damaged cells, pathogens, toxic compounds, or irradiations [ 9 ]. The vascular theory suggests a sudden interruption of blood circulation to parts of the brain, encompassing both ischemic and hemorrhagic stroke [ 10 , 11 ]. In Ischemic stroke, when the blood supply to parts of the brain is interrupted, the theory implies that stroke can occur due to blockages caused by factors affecting atherosclerosis, thrombosis, embolism, or blood clotting.…”
Section: Introductionmentioning
confidence: 99%